Determinants of traditional eye practices amongst rural dwellers in the Asikuma Odoben Brakwa District, Ghana - Eugene B. Enimah; Urvashni Nirghin; Samuel B. Boadi-Kusi; Micheal Ntodie (African Vision and Eye Health, 2022)
Background: In Ghana and other developing countries, people resort to other means of eye care apart from the orthodox treatment given by eye care practitioners.